2003
DOI: 10.1034/j.1600-0404.2003.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy: analysis of patients with dual pathology

Abstract: 15.4% had dual pathology. The dual pathology was almost exclusively seen in patients whose lesions were congenital, or occurred early in life, suggesting that the hippocampus is more vulnerable and more readily develops HS in early childhood. Resections, including the lateral and mesial temporal structures led to a favorable outcome with no mortality and little morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 11 publications
3
53
0
6
Order By: Relevance
“…Although the recognized association of callosal and hippocampal abnormalities was seen in our patients, we did not see this combination as a separate subgroup. 1,3,[29][30][31] The arrested hippocampal rotation is likely to be due to secondary effects of abnormal development, though we acknowledge it could be part of the same genetic defect that arrests the migration of neural progenitor cells. 32 Four patients had callosal hypertrophy with dysplastic splenia, hippocampal dysplasia, and abnormal Sylvian fissures.…”
Section: Associated Malformationsmentioning
confidence: 99%
“…Although the recognized association of callosal and hippocampal abnormalities was seen in our patients, we did not see this combination as a separate subgroup. 1,3,[29][30][31] The arrested hippocampal rotation is likely to be due to secondary effects of abnormal development, though we acknowledge it could be part of the same genetic defect that arrests the migration of neural progenitor cells. 32 Four patients had callosal hypertrophy with dysplastic splenia, hippocampal dysplasia, and abnormal Sylvian fissures.…”
Section: Associated Malformationsmentioning
confidence: 99%
“…Dual pathology does not merely indicate the anatomical coexistence of HS with an extrahippocampal lesion, but also pathophysiological mechanisms such as the kindling phenomenon and secondary hippocampal epileptogenesis [9,10,11,12]. Dual pathology is almost exclusively found in patients with congenital extrahippocampal lesions or occurs early in life, suggesting that the hippocampus is more vulnerable and more likely to develop HS in early childhood [3]. Raymond et al [13] proposed three possible explanations for the dual occurrence of HS and extrahippocampal cortical dysgenesis (CD): (1) the presence of CD predisposes to prolonged febrile convulsions in childhood, leading to HS; (2) CD induces repeated seizures that causes secondary hippocampal damage; and (3) they share a common embryonic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Salanova et al [3] showed that resection of both lesions led to an excellent outcome, with 70.2% of patients becoming seizure-free and 21.6% having only rare seizures, while none of the patients with non-resected extrahippocampal lesions became seizure-free. Furthermore, Li et al [11] demonstrated that 73% of patients with both lesions resected became seizure-free, compared with 20% of patients with only the medial temporal structures resected and 12.5% of patients with only the extrahippocampal lesion resected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, brain functional neuroimaging studies may be useful [2][3][4][5][6][7]. Many studies have reported the usefulness of interictal/ictal cerebral blood flow single photon emission computed tomography (SPECT) [8][9][10][11][12] and interictal 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) [2,3,7,10,13]. 123 I-iomazenil SPECT (IMZ-SPECT) was developed based on biochemical abnormalities existing in the epileptogenic brain lesion, and is able to detect the original epileptic focus effectively in the interictal state [14,15].…”
Section: Introductionmentioning
confidence: 99%